Social Competence in Children with Borderline Intellectual Functioning: Delayed Development of Theory of Mind Across All Complexity Levels - Baglio, Gisella; Blasi, Valeria; Sangiuliano Intra, Francesca; Castelli, Ilaria; Massaro, Davide; Baglio, Francesca; Valle, Annalisa; Zanette, Michela; Marchetti, Antonella (Frontiers in Psychology, 2016)
Borderline intellectual functioning (BIF) is characterized by heterogeneous cognitive difficulties, with an intelligence quotient (IQ) between 70 and 85 points, and a failure to meet the developmental and sociocultural standards for personal independence and social responsibility required in daily life. The fact that this population still remain a marginal clinical category, with no ad hoc diagnostic and therapeutic approaches, has stimulated the present research. Our goal was to study children with BIF investigating the development of Theory of Mind (ToM) as a pillar of social competence. Children with BIF (N = 28, 16 male/12 female, and mean age 9.46 ± 1.26 years) and children with typical development (TD; N = 31, 17 male/14 female; mean age 8.94 years ± 0.99) underwent a neurocognitive assessment and a ToM assessment. Children with BIF showed a significant lower performance across all the levels of ToM development investigated compared to the control group, and a correlation between executive functions and the advanced levels of ToM reasoning. These results constitute a first step in the direction of defining the clinical profile of children with BIF concerning ToM development, opening the way to future interventions in order to support the developmental evolution of this population in an adaptive direction.